İntestinal Obstrüksiyona Neden Olan Dev Mezenterik Hemanjioma; Olgu Sunumu - Aliosmanoğlu, İbrahim; Gül, Mesut; Ülger, Burak Veli; Tekeş, Fırat; Hakseven, Musluh; Büyükbayram, Hüseyin (Fırat University, 2013)
Mezenterik hemangioma, nadir ve sıklıkla erken yaşlarda görülen benign bir lezyondur. Hastalar sıklıkla gastro-intestinal kanama ve obstrüksiyon bulgularıyla kliniğe başvururlar. Onsekiz yaşında intestinal obstrüksiyon bulgularıyla hastaneye başvuran, radyolojik görüntüleme ve histopatolojik değerlendirme sonucu mezenterik hemanjiom tanısı alan olgu, nadir görülmesi nedeniyle sunulmuştur.

Mesenteric hemangioma is a rare benign lesion commonly seen in the early ages. They usually apply to the clinic with findings of gastro-intestinal bleeding and obstruction. The case of an 18 year old patient applying to the hospital with findings of obstruction and after radiologic imaging and histopathologic examination, diagnosed with mesenteric hemangioma is presented because it is rare.
Giant Mesenteric Hemangioma Causing Intestinal Obstruction: A Case Report